Czech Republic : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This paper describes economic developments in the Czech Republic during 1990-95. In 1991-93, quick progress was made in containing inflation, rebuilding foreign reserves, and restoring confidence in economic policies; and this was followed by resumption of growth in 1994. Financial and political stability and continued progress toward a market economy attracted large capital inflows in 1993-95. In spite of attempts to sterilize these inflows, monetary growth was rapid and fueled a boom in domestic demand, which in turn widened the current account deficit and maintained inflation at relatively high levels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet